Anti-listeria Activities of Linalool and Its Mechanism Revealed by Comparative Transcriptome Analysis - Gao, Zhipeng; Van Nostrand, Joy D.; Zhou, Jizhong; Zhong, Weiming; Chen, Kangyong; Guo, Jiajing (Frontiers in Microbiology, 2019)
Listeria monocytogenes, which causes serious foodborne infections and public health problems worldwide, is one of the most important foodborne pathogens. Linalool has been identified as an antimicrobial agent against some microorganism, but its mechanism of action is currently unclear. Here, we investigated the efficacy of linalool against L. monocytogenes while planktonic and as a biofilm and explored potential mechanisms of action. Linalool exhibited strong anti-listeria activity in the planktonic stage. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) observations revealed seven stages were classified of cells at microscopic level. Mesosome-like structures were observed for the first time in L. monocytogenes after linalool treatment. Linalool also showed significant anti-biofilm activity through both dispersal and killing of cells in the biofilm based on confocal scanning laser microscopy (CLSM) and SEM imaging, crystal violet staining, XTT and COMSTAT assays. Moreover, comparative transcriptome analysis demonstrated many potential mechanisms of action for linalool and some important pathways were screened out through the analysis of GO enrichment and KEGG. Our study provides evidence that linalool exhibits a strong antimicrobial activity against both the planktonic and biofilm forms of L. monocytogenes and gives insight into its mechanism of action.